An eco-friendly approach for heavy metal adsorbent regeneration using CO2-responsive molecular octopus. (October 2017) - Bai, Yu; Liang, Yen Nan; Hu, Xiao
Abstract: Perennial problems of adsorption in wastewater treatment include adsorbent recycling, generation of waste sludge and secondary pollution because harmful concentrated acids, bases or strong chelators are often used for adsorbent regeneration and adsorbate recovery. We report, for the first time, an eco-friendly regeneration concept demonstrated with a CO2 -responsive octopus-like polymeric adsorbent. Various heavy metals can be scavenged at very high Q e by such adsorbent through coordination. Most importantly, the rapid and complete regeneration of the adsorbent and recovery of the heavy metal ions can be readily achieved by CO2 bubbling within a few minutes under mild conditions, i.e., room temperature and atmospheric pressure. The adsorbent can then be restored to its adsorptive state and reused upon removal of CO2 by simply bubbling another gas. This eco-friendly, effective, ultra-fast and repeatable CO2 -triggered regeneration process using CO2 -responsive adsorbent with versatile structure, morphology or form can be incorporated into a sustainable closed-loop wastewater treatment process to solve the perennial problems. Graphical abstract: Highlights: Using CO2 as an eco-friendly trigger for adsorbent regeneration and heavy metal recovery. CO2 -responsive octopus-like adsorbent enables efficient adsorption and mild but complete regeneration. Six different heavy metals are used to study the capability and efficiency of adsorption and regeneration. Conceptual toxic chemical-free closed-loop wastewater treatment system.